(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Surface modified PAN nanofibers were prepared by reaction between PAN electrospun nanofibers and hydroxylamine hydrochloride. The prepared nanofibers were used as matrix for lead ions adsorption. Micrographs of modified normal PAN fibers and PAN nanofibers were observed by Field Emission Scanning Electron Microscope (FESEM), and Fourier Transform Spectroscopy (FTIR) spectra of the surface modified PAN nanofibers were recorded. The adsorption capacity of modfied PAN nanofibers and modified normal PAN fibers were calculated, and the adsorption isotherm of Pb^2+ on the modified PAN nanofibers was studied. According to the results of experiment, surface modified PAN nanofibers had excellent adsorption capacity for lead ions.